Cauchy or not Cauchy? New goodness-of-fit tests for the Cauchy distribution - Bruno Ebner; Lena Eid; Bernhard Klar (Statistical Papers, 2022)
We introduce a new characterization of the Cauchy distribution and propose a class of goodness-of-fit tests for the Cauchy family. The limit distribution is derived in a Hilbert space framework under the null hypothesis. The new tests are consistent against a large class of alternatives. A comparative Monte Carlo simulation study shows that the test is a good competitor for the state of the art procedures, and we apply the tests to log-returns of cryptocurrencies.
Keywords: 510; Goodness-of-fit; Cauchy distribution; Hilbert-space valued random elements